Selective and sensitive determination of amlodipine in binary mixtures using a nanomaterial-assisted molecularly imprinted electrochemical sensor - Bekmez, Berfu; Budak, Fatma; Cetinkaya, Ahmet; Ozkan, Sibel A. (Elsevier, 2026)
Cardiovascular disease, one of the leading causes of death in developing countries, is mainly caused by the combination of arterial hypertension and dyslipidemia as major risk factors. Amlodipine (AML) is a calcium channel blocker that inhibits extracellular calcium influx across the membranes of myocardial and vascular smooth muscle cells, thereby reducing contraction and dilating coronary and systemic arteries. This study aimed to design a nanoparticle-supported molecularly imprinted polymer (MIP)-based electrochemical sensor with selective and sensitive sensitivity for the quantitative analysis of both binary drug mixtures and AML. The modified sensor was produced by the electropolymerization (EP) method in the presence of 4-aminobenzoic acid (4-ABA) as the functional monomer, pyrrole (Py) as the copolymerization monomer, and the target molecule AML. The incorporation of silver nanoparticles (AgNPs) into the MIP-based electrochemical sensor increased its active surface area and porosity. The AML/4-ABA-co-Py@AgNPs/MIP-GCE sensor was characterized both electrochemically (electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV)) and by surface morphology (scanning electron microscopy (SEM)). The quantification of AML was performed using differential pulse voltammetry (DPV) with the direct method in a 5.0 mM [Fe(CN)6]3-/4 solution, yielding a linear range of 0.1-1.0 pM. The applicability and accuracy of the sensor were evaluated by recovery studies in tablet forms containing binary mixtures. In addition, to demonstrate the sensor's selectivity, a selectivity study was performed in the presence of components with chemical structures similar to those of AML, and its high selectivity was confirmed by the relative suppression factors for AML. In conclusion, this newly developed sensor for AML offers many advantages, such as selective, sensitive, fast, and inexpensive analysis.
Keywords: Amlodipine; Electrochemical sensors; Molecularly imprinted polymers; Detection